Harmonizing Modernity with Tradition: Report on Indonesian Delegation of Teachers and Pesantren Heads to Japan 2007 - Subhan, Arief (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
The 2007 visit was themed